Evaluating rice germplasm for iron and zinc concentration in brown rice and seed dimensions - Agarwal, Surekha; Batchu, Anil K; Babu, A Prasad; B P Mallikarjuna Swamy, B P; Longvah, T; Sarla, N (Journal of Phytology, 2012)
The lack of micronutrients such as Fe and Zn in staple food crops is a widespread nutrition and health problem in developing countries. Biofortification is one of the sustainable approaches, for improving the Fe and Zn content and their bioavailability in rice grain. Screening germplasm for Fe and Zn content is the initial step of biofortification. We analyzed brown rice of 126 accessions of rice genotypes for Fe and Zn concentration. Iron concentration ranged from 6.2 ppm to 71.6 ppm and zinc from 26.2 ppm to 67.3 ppm. Zn concentration and grain elongation (-0.25) was significantly correlated. The wild accessions had the highest Fe and Zn. Thus, wild species are a good source for biofortification of popular rice cultivars using conventional, acceptable, non transgenic methods.Â Â 